Studi Deskriptif Hasil Karya Seni Montase Pada Bidang Tiga Dimensi Pada Siswa Sekolah Dasar - Nurhanifa Auliawati; Hasnawati Hasnawati; Dwi Anggraini (JURIDIKDAS, 2021)
This study aims to describe the process of making montage art in three dimensional fields and montage works in three dimensional fields in class IV B elementary school Bengkulu City.This type of research is qualitative, with participant observation techniques, and qualitative descriptive method. The research subjects were all students of class IV B 01 elemnetary school in Bengkulu City, totaling 28 students. The research instrument used was a human instrument (the researcher himself), by using observation guidelines and interview guidlines. Data collection techniques in the form of observation, interview, and documentation. Data analysis was carried out during the process of making the work and after the work was finished by referring to the fine arts elements and the principles of fine arts. Research results are (1)the process of making montage artwork in a three dimensional field begins with preparing the tools and materials used, namely glue, pictures, bamboo, and scissors, followed by the implementation of making works from cutting images, collecting images, combining pieces of pictures, and placing pieces of images on bamboo. Montage works in three dimensional field that are made based on the elements of fine arts and the principles of fine arts, namely the elements of point, lines, fields, shapes, colors, textures, dark light, space and light. Then, the principle of unity, balance, rhythm, emphasis, proportion, and harmony.Keywords: Descriptive, Montage Art, Three Dimension